Explique esses cálculos por favor.. Potenciação [-2^-2]^3=-1/64 [-2^3]^-2=1/64 [-2^-3]^2=1/64
samuelslv:
completei
Soluções para a tarefa
Respondido por
5
Ola Samuel
(-2)^-2)^3 = (1/4)^3 = 1/64
(-2^3)^-2 = (-8)^-2 = (-1/8)^2 = (-1)^2/(8^2) = 1/64
((-2)^-3)^-2 = (-1/8)^2 = 1/64
(-2)^-2)^3 = (1/4)^3 = 1/64
(-2^3)^-2 = (-8)^-2 = (-1/8)^2 = (-1)^2/(8^2) = 1/64
((-2)^-3)^-2 = (-1/8)^2 = 1/64
Perguntas interessantes
Inglês,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Filosofia,
1 ano atrás
Português,
1 ano atrás
História,
1 ano atrás
Sociologia,
1 ano atrás